Exchange rate misalignment and capital inflows: an endogenous threshold analysis for Malaysia - Mohd Sidek , Noor Zahirah; Yusoff, Mohammed; Munir, Qaiser (2009)
This study presents an attempt to investigate the impact of exchange rate misalignment on capital inflows in Malaysia. Specifically, a precise threshold value is estimated to examine when exchange rate misalignment suppresses capital inflows. To pursue these objectives, this study relies on the endogenous threshold analysis as of Hansen (1996, 2000). Results suggest that misalignment in terms of currency overvaluation, has a negative and significant effect when overvaluation is more than 15 percent. This estimate is consistent and robust despite the changes in the choice of explanatory variables.